Jumping performance and take-off efficiency correlation with the basic anthropometric parameters in female volleyball players - Jandová, Soňa (Acta Gymnica, 2021)
Background: Vertical jump height and body height are almost universally recognised as determinant factors in elite volleyball performance. Objective: The purpose of this study was to assess the correlation between basic anthropometric parameters (body height and body weight) and jumping performance in a group of 16 female volleyball players (age 19.14 ± 5.52 years, height 1.80 ± 0.06 m, weight 69.81 ± 6.85 kg) and in a control group of 15 female university students (age 22.90 ± 0.83 years, height 1.70 ± 0.05 m, weight 61.70 ± 8.23 kg). Methods: The Quattro Jump 9290BA force platform system (Kistler, Winterthur, Switzerland) was used to test jumping performance in single vertical jumps (squat jump, countermovement jump) and 45-s continuous jumps. In single jumps, jump height was analysed and during the 45-s continuous jumps the maximal and mean jump height, the average contact time and the fatigue index were evaluated. The efficiency of the conversion of mechanical work into mechanical energy at the moment of take-off was calculated. Results: No significant influence of body height and body weight was found in the jumping performance in the squat jump and countermovement jump. In continuous jumps, a significant correlation was found between body height and fatigue index in the volleyball players. In the control group, in most of the tests moderate correlation between body height and jump height was observed. In the volleyball players, rather low values of efficiency of take-off (23.67 ± 2.64%) were calculated. The values in the control group were even lower. Conclusions: Nowadays, many volleyball coaches choose individuals mainly according to body height, but it is important that the talent identification process should also consider jumping abilities in the simple jumps and in continuous jumps. All these parameters should help coaches choose the right players for the appropriate position and role in the team.
Keywords: Young Adult; Research; volejbal; mladý dospělý; Athletes; sportovci; Adult; Body Height; dospělí; antropometrie; tělesná výška; skokanský výkon; výzkum; Body Weight; Volleyball; Anthropometry; lidé; ženské pohlaví; sportovní výkon; Humans; Female; Athletic Performance; tělesná hmotnost